PENDIDIKAN KONTRUKTIVISTIK DALAM PENGEMBANGAN KEBERBAKATAN ANAK - Ujam Jaenudin (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2010)
Theoretically, the constructive theory uses the cognitive theory as supposition. The constructive theory explains that knowledge is set and developed because of interaction between individual and its environment. Therefore, knowledge is not a unit in constructive frame. Knowledge is interaction between individual and its environment that has objective and subjective component. The constructive learning in developing talented child can be based to increase new knowledge. The talented child in constructive frame enable to adapt the information or knowledge learned by the teacher.